The aesthetics of videogame music - Sweeney, MR (2014)
The videogame now occupies a unique territory in contemporary culture that offers a new perspective on conceptions of high and low art. While the fear that the majority of videogames 'pacify' their audience in an Adornian "culture industry" is not without justification, its reductionism can be countered by a recognition of the diversity and aesthetic potential of the medium. This has been proposed by sociologist, Graeme Kirkpatrick, although without close attention to the role of music. Videogame music often operates in similar ways to music in other mixed-media scenarios, such as film, or opera. In the same way that film music cannot be completely divorced from film, videogame music is contingent on and a crucial part of the videogame aesthetic. However, the interactive nature of the medium—its différance—has naturally led to the development of nonlinear musical systems that tailor music in real time to the game's dynamically changing dramatic action. Musical non-linearity points beyond both music and videogames (and their respective discourses) toward broader issues pertinent to contemporary musicology and critical thinking, not least to matters concerning high modernism (traditionally conceived of as resistant to mass culture). Such issues include Barthes's "death of the author", the significance of order/disorder as a formal spectrum, and postmodern conceptions and experiences of temporality. I argue that in this sense the videogame medium—and its music—warrants attention as a unique but not sui generis aesthetic experience. Precedent can be found for many of the formal ideas employed in such systems in certain aspects of avant-garde art, and especially in the aleatoric music prevalent in the 1950s and 60s. This thesis explores this paradox by considering videogames as both high and low, and, more significantly, I argue that the aesthetics of videogame music draw attention to the centrality of "play" in all cultural objects.